Infektiologische und immunologische Aspekte bei Kinderwunsch - Kuon, Ruben-Jeremias; Daniel, Volker; Gaiser, Timo; Toth, Bettina (Gynäkologische Endokrinologie, 2018)
Despite advanced techniques in reproductive medicine, including preimplantation genetic diagnosis, in some cases implantation fails even after repeated transfer of a morphologically and genetically normal embryo. This frustrating complication is called recurrent implantation failure (RIF). In addition, approximately 1-3% of couples are affected by recurrent spontaneous miscarriage (RSM). A causative factor is diagnosed in only approximately half of these cases. Recently, infectiological and immunological aspects have come into focus of diagnostics in couples affected by RIF or RSM. In addition to autoimmune factors, such as the antiphospholipid syndrome, the role of peripheral and uterine natural killer cells in implantation and miscarriage is highlighted. The latest data also indicate chronic endometritis as a risk factor for both RIF and RSM. Whether there is an overlap in the pathogenesis of RIF and RSM is currently being investigated